Political Economy of Sabah’s Economic Development: Economic Policy and Federal-State Relations / Firdausi Suffian ... [et al.] - Suffian, Firdausi; Puyok, Arnold; Mansur, Kasim; Abdul Majid, Azmi (2021)
The formation of Malaysia in 1963 is one of the important histories in Southeast Asia. Despite the formation is a controversial one because other nations like the Philippines and Indonesia pose threats to the union however the Borneo states (Sabah and Sarawak) and the Federation of Malaya managed to materialise the formation of Malaysia with much deliberation and diplomacy. Cobbold commission has been instrumental to show the people in Borneo state agreed to the 'Malaysia project', though only one-third of the population favours the union, the decision incorporating Sabah to form a federation of Malaysia has benefited the state to a certain extent. The main purpose of Sabah's agreement to form Malaysia is that the federation will ensure special rights of the state, which is spelled out in the federal constitutions, and improve socio-economic development. The formation of Malaysia also means the country has expanded its domestic market, utilisation of resources, land, and labour. The central government must ensure sufficient growth of every state, while it is the right of the state to demand strategic development to improve socio-economic welfare.